2./ 8. asır Mısır hadis halkaları - Gönüllü, Baki (My University, 2023)
Hadis tarihinin erken dönemi sayılabilecek olan hicri ilk üç asırdaki bütün resmi doğru bir şekilde anlayıp analiz edebilmek için bölgesel ve zamansal çalışmalara ihtiyaç vardır. Söz konusu ihtiyaçtan hareketle bu çalışmada, 2./ 8. asır Mısır hadis halkaları ele alınmıştır. İlk olarak hicri ilk iki asırda öne çıkan ilimler ve aralarındaki ilişkiler tasvir edilmiş, daha sonra da Mısır’da yaşadığı tespit edilen 605 râvi yaşadıkları dönem, rivayet sayıları, güvenilirlik durumları, etnik kökenleri, geçim vasıtaları ve itikadi eğilimleri gibi farklı açılardan tahlile tabi tutularak bölgenin ilmî yapısı ortaya konmuştur. Ardından Ehl-i hadîs halkalarının tespiti için geliştirilen metottan istifade edilerek, mezkûr zaman diliminde Mısır’da Yezîd b. Ebî Habîb, Abdullah b. Lehîa, Leys b. Sa‘d ve Abdullah b. Vehb’e ait dört asli halka; Süleyman b. Amr, Saîd b. Ebî Hilal, Muâviye b. Salih ve Yahya b. Eyyûb’a ait de dört tali halka tespit edilmiş ve halka sahipleriyle mensupları arasındaki ilişkiler de detaylı bir şekilde incelenmiştir.

In order to accurately understand and analyze the entire official early period of hadith history, which can be considered the first three centuries of A.H., regional and temporal studies are needed. Based on this need, this study focuses on the hadith circles in Egypt during the 2nd/ 8th century. First, the sciences prominent during the first two centuries of A.H. and their relationships are described. Then, 605 narrators who were identified as living in Egypt are analyzed from various perspectives such as the period they lived in, the number of narrations, their reliability, ethnic backgrounds, livelihoods, and doctrinal tendencies, revealing the scholarly structure of the region. Subsequently, the method developed for identifying the circles of Ahl al-hadith is utilized, and during the mentioned time frame in Egypt, four primary circles attributed to Yazīd b. Abī Ḥabīb, ͑Abdullah b. Lahī ͑a, Layth b. Sa͑ d, and ͑Abdullah b. Wahb, as well as four secondary circles attributed to Suleiman b. ͑Amr, Sa ͑īd b. Abī Hilāl, Mu ͑āwiya b. Ṣāliḥ, and Yaḥyā b. Ayyūb, are identified and the relationships between circle owners and their members are examined in detail.
Hadith circles of Egyptian in the second/ eighth century
Keywords: Circle; Egypt; Hadis; Hadis Halkaları Hadith; Hadith; Hadith Circles; Halka; Mısır